The Relationship Between Consumer Behavior And Tourists’ Travel Decisions In Malang City, East Java - Kartika Windrajanti; Yatnanta Ramadhana; Eri Widiyanto (CV Putra Publisher, 2026)
Tourism is a rapidly growing sector whose development is closely shaped by consumer behavior. In this study, consumer behavior refers to the way tourists search for information, form destination preferences, and evaluate perceived value, whereas a travel decision refers to a tourist’s actual choice to undertake a tourist trip to a particular destination. This study aims to analyze the relationship between consumer behavior and tourists’ travel decisions in Malang City, East Java. A quantitative survey was conducted on 100 respondents selected through accidental sampling, since the population size was unknown. Data were collected using a Likert-scale questionnaire and analyzed with SPSS through validity, reliability, and normality tests, followed by simple linear regression. The results show that consumer behavior has a significant relationship with travel decisions, with a significance value of 0.001 and a coefficient of determination of 37.4 percent. These findings indicate that consumer behavior plays an important role in shaping tourists’ decisions to travel, so that understanding it is essential for developing marketing strategies and managing tourist destinations. This study contributes to consumer behavior research in the tourism sector and serves as a reference for destination managers in understanding tourist behavior